2015
DOI: 10.1371/journal.pone.0145717
|View full text |Cite
|
Sign up to set email alerts
|

The Immunodominance Change and Protection of CD4+ T-Cell Responses Elicited by an Envelope Protein Domain III-Based Tetravalent Dengue Vaccine in Mice

Abstract: Dengue is the leading cause of mosquito-borne viral infections and no vaccine is available now. Envelope protein domain III (ED3) is the major target for the binding of dengue virus neutralizing antibodies; however, the ED3-specifc T-cell response is less well understood. To investigate the T-cell responses to four serotypes of dengue virus (DENV-1 to 4), we immunized mice using either a tetravalent ED3-based DNA or protein vaccine, or combined both as a DNA prime-protein boost strategy (prime-boost). A signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…The other two are on envelope protein residues 295 to 309 (D1-1, D2-1, and D3-1) and 349-363 (D1-10, D2-10, and D3-10) and are both recognized by CD4 + T cells ( Fig. 5C ), consistent with previous reports 52 53 54 . CD4 + T cells reacted to peptides derived from 4 serotypes of dengue virus in vaccinated mice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The other two are on envelope protein residues 295 to 309 (D1-1, D2-1, and D3-1) and 349-363 (D1-10, D2-10, and D3-10) and are both recognized by CD4 + T cells ( Fig. 5C ), consistent with previous reports 52 53 54 . CD4 + T cells reacted to peptides derived from 4 serotypes of dengue virus in vaccinated mice.…”
Section: Discussionsupporting
confidence: 91%
“…Another region is on envelope protein residues 313 to 327 (D4-4) and is recognized by CD4 + T cells ( Fig. 5C ), which has been reported in our previous study 52 . The other two are on envelope protein residues 295 to 309 (D1-1, D2-1, and D3-1) and 349-363 (D1-10, D2-10, and D3-10) and are both recognized by CD4 + T cells ( Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…ED3, with a length of ∼100 amino acids, has been reported to contain serotype-specific neutralizing antibody epitopes (52) and has been used as the target antigen of dengue vaccine (53)(54)(55)(56)(57)(58). In previous studies of ED3-based tetravalent DNA or MV vector vaccines, we identified serotype-specific and crossreactive CD4 + T-cell epitopes within ED3 in BALB/c (H-2 d ) and C57BL/6 (H-2 b ) mice and observed immunodominance changes among these T-cell epitopes (47,59). For example, in BALB/c mice, the tetravalent dengue ED3-based DNA vaccine induced one cross-reactive CD4 + T-cell epitope shared by DENV-1,−2, and−3 and one serotype-specific CD4 + T-cell epitope to DENV-4.…”
Section: Discussionmentioning
confidence: 96%
“…T-cell subunit vaccines are safer, as they elicit immune responses based on the minimal pathogen-specific antigenic elements, conserved across multiple pathogenic strains and exclude self (host) antigens [16]. Indeed, T-cell epitopes have been shown as potential vaccine candidates in flaviviruses such as Dengue and Yellow fever [20][21][22][23][24][25][26][27]. Therefore, an immunoinformatics approach was implemented in the present study to detect minimal T-cell epitopes from the translated ssRNA (+) genome of Zika virus, capable of inducing cell-mediated immunity in humans.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%